Automation System of Water Circulation and Fish Feeding in Tilapia Fish Pond with Solar Panel Source - Iriani, Juli; Dharma, Surya; Gunoro; Sitorus, Nobert; Rumahorbo, Priansus Rhein; Ridho; Cholish; Wahyudi (International Journal of Applied Research and Sustainable Sciences, 2024)
Tilapia cultivation requires good management of water quality and proper feeding to ensure optimal fish growth. One of the main challenges in this process is maintaining the water pH level within ideal limits and providing feed according to the needs of the fish based on their size. In addition, limited access to electricity in some locations makes fish pond management less efficient. This study aims to design an automated water circulation system that is regulated based on the water pH level and automatic feeding according to the needs of the fish, by utilizing solar panels as a power source. This system uses a pH sensor to monitor water conditions in real time and regulate water circulation to maintain ideal pH levels. Feeding is regulated based on the size and number of fish to ensure optimal feed efficiency and fish growth. This system is powered by solar panel energy, so it can operate independently without relying on conventional electricity networks. Test results show that the system is able to maintain water pH stability and automate feeding with high accuracy, while utilizing renewable energy effectively. The use of solar panels not only reduces dependence on electricity, but also reduces operational costs and supports environmental sustainability. This system is expected to increase the efficiency and productivity of tilapia cultivation, especially in areas with limited access to electricity.